Electrolyte derangements in critically ill children receiving balanced versus unbalanced crystalloid fluid resuscitation - Stanski, Natalja L.; Gist, Katja M.; Pickett, Kaci; Brinton, John T.; Sadlowski, Jennifer; Wong, Hector R.; Mourani, Peter; Soranno, Danielle E.; Kendrick, Jessica; Stenson, Erin K. (BMC nephrology, 2022)
Background Adult studies have demonstrated potential harm from resuscitation with 0.9% sodium chloride (0.9%NaCl), resulting in increased utilization of balanced crystalloids like lactated ringers (LR). The sodium and potassium content of LR has resulted in theoretical safety concerns, although limited data exists in pediatrics. We hypothesized that use of LR for resuscitation would not be associated with increased electrolyte derangements compared to 0.9%NaCl. Methods A prospective, observational cohort study of critically ill children who received ≥ 20 ml/kg of fluid resuscitation and were admitted to two pediatric intensive care units from November 2017 to February 2020. Fluid groups included patients who received > 75% of fluids from 0.9%NaCl, > 75% of fluids from LR, and a mixed group. The primary outcome was incidence of electrolyte derangements (sodium, chloride, potassium) and acidosis. Results Among 559 patients, 297 (53%) received predominantly 0.9%NaCl, 74 (13%) received predominantly LR, and 188 (34%) received a mixture. Extreme hyperkalemia (potassium ≥ 6 mmol/L) was more common in 0.9%NaCl group (5.8%) compared to LR group (0%), p 0.05. Extreme acidosis (pH > 7.1) was more common in 0.9%NaCl group (11%) compared to LR group (1.6%), p 0.016. Conclusions LR is associated with fewer electrolyte derangements compared to 0.9%NaCl. Prospective interventional trials are needed to validate these findings.